PENGEMBANGAN MEDIA UBATU BERBANTUAN ETNOSAINS MENGGUNAKAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN SELF-REGULATED SISWA KELAS IV SEKOLAH DASAR - Tahliya, Yenik Ulfiyatut; Amalia, Shofi Nur; Fatih, Mohamad (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to develop the UBATU learning media based on ethnoscience integrated with the Problem-Based Learning (PBL) model to examine students’ self-regulated learning abilities, including their metacognitive, motivational, and behavioral aspects in accordance with current educational developments. The research employed a Research and Development (R&D) approach using the ADDIE development model. The results showed that the average score from the material expert validation was 94.6%, categorized as valid, while the media expert validation obtained an average score of 91.94%, categorized as highly valid. The product feasibility test achieved an average score of 97.60%, indicating that the media was highly feasible for classroom use. Furthermore, students’ pre-questionnaire score totaled 660, and the post-questionnaire score reached 928, resulting in an N-gain score of 0.71, which falls into the high category for improving students’ self-regulated learning during the learning process. In conclusion, the developed UBATU media is valid for use in the learning process and effectively enhances the self-regulated learning abilities of fourth-grade elementary students.